Chlorella vulgaris and Spirulina platensis: Their Nutrient Contents and Bioactive Compounds for Improving Poultry Productivity - Sugiharto Sugiharto (Indonesian Center for Animal Research and Development, 2020)
Poultry industry are facing many challenges and osbtacles especially on the supply of feed ingredients, medicines, feed supplements and additives. The high price of protein source-feed ingredients has encouraged nutritionists to explore and utilize alternative protein source-feed ingredients for poultry. This review provides an overview of their nutritional and bioactive contents and the use of microalgae, Chlorella vulgaris and Spirulina platensis in poultry feed based on recent literature studies and their potential development and utilization in Indonesia. The microalgae Chlorella vulgaris dan Spirulina platensis have very high protein content that are potential as a protein source in poultry rations. In addition, Chlorella vulgaris and Spirulina platensis also contain several bioactive compounds that can be used as alternatives to antibiotics growth promoter and synthetic antioxidants for poultry. Indonesia has a great potential for the production of Chlorella vulgaris and Spirulina platensis, however massive cultivation and economies of scale have not yet been carried out. Such conditions make Chlorella vulgaris and Spirulina platensis less profitable as protein sources, but more likely as growth-promoting additives or antioxidants for poultry in Indonesia.